Epidemiology of diabetes mellitus, pre-diabetes, undiagnosed and uncontrolled diabetes in Central Iran: results from Yazd health study - Masoud Mirzaei; Masoud Rahmaninan; Mohsen Mirzaei; Azadeh Nadjarzadeh; Abbas Ali Dehghani tafti (BMC, 2020)
Abstract Background Over the past few decades, the prevalence of Diabetes Mellitus (DM) has risen rapidly in Iran and other low and middle-income countries. We investigated the prevalence of DM, pre-diabetes, undiagnosed and uncontrolled diabetes and its relationship with some associated socioeconomic factors in the Yazd Greater Area in Iran. Methods Yazd Health Study is a longitudinal study conducted to determine the prevalence of non-communicable disease and related risk factors. In a two-step cluster sampling, 10,000 adults aged 20-69 years (200 clusters) were selected. In the recruitment phase, DM was considered if the patients had been either diagnosed DM by a physician or had fasting blood glucose ≥ 126 mg/dL. Chi square test was used for categorical variables to evaluate the differences and logistic regression model was applied to determine the predictors of diabetes.. P-value < 0.05 considered statistically significant. Results Of the 9965 individuals recruited, the crude self-reported prevalence of DM was 14.1% (95% CI: 13.4-14.7). The prevalence was higher in women than men (15.6 vs.12.4%), significantly. The age-standardized prevalence of DM was 8%. The prevalence was 14.9% in Yazd local people and 8.6% in those residents migrated from other provinces (P < 0.0001). We showed a significant association between DM prevalence and age, education, marital status, unemployment, insurance status, and positive family history (P < 0.0001). The prevalence of DM diagnosed by phycisians was 16.1% in participants (age-standardized prevalence: 8.3%). The subset analysis showed that 4.8% of patients were not aware of their disease. The prevalence of pre-diabetes was 25.8%. Of those with diabetes, 58.3% were not adequately controlled, which is not statistically significant with socio-economic status. Conclusion The current study showed a high prevalence of DM in Yazd Greater Area which is closely related to some socio-demographic factors. The high prevalence of pre-diabetes is alarming. Effective strategies for DM prevention should be introduced. The majority of people with diabetes are aware, but half of them are not controlled. The ineffective care plan currently in use, should be reviewed. Patients needs to be encouraged to improve their lifestyle. Active follow-up of patients is recommended to ensure continuity of care.